'Equality on the sea': interrogating LGBTQ privilege in the tourism discourse of Africa's 'gay capital'. (5th September 2017) - Comer, Joseph
Abstract : In this paper, I examine LGBTQ tourism discourse about Cape Town, South Africa, which is often declared the 'gay capital of Africa'. The paper considers the implications of such claims and how, in the specific case of Cape Town, apparently playful rhetorics obscure deep-seated inequalities under the guise of visibility, equality and globality. Using a multimodal critical discourse analysis informed by queer theory, my paper examines the recurrent linguistic and visual production of these rhetorics in a range of LGBTQ tourism marketing materials, before focusing on the website of one key agent: Out2Africa. Ultimately, I demonstrate how, contrary to the superficially progressive and cosmopolitan discourses of LGBTQ tourism, equality is increasingly represented in consumer media as an individual attainment typified by privileged mobility rather than any true social condition. Under the sway of neoliberal capitalism, mobility is a commodity, identity, and metonym for pride, and equality becomes a slogan.